Literature Review : Hydrotherapy Reduce Blood Pressure among Hipertensive Clients - Yasmina Izzat; Muhamad Jauhar; Fajar Surachmi (Journal of Nursing Science Update (JNSU), 2021)
Hypertension is a cardiovascular disease that has been linked to a number of public health issues. This is due to unhealthy lifestyles and cellular and tissue physiological function impairment. Hydrotherapy is a non-pharmacological intervention that can lower blood pressure. As long as the patient is taking antihypertensive medications, this therapy becomes complementary. This study aims to describe the use of hydrotherapy that lowers blood pressure in hypertensive patients. The research design used is a literature review of national and international indexed journals. The databases used include ProQuest, GALE, OneSearch, RAMA, SINTA, and Google Scholar by using keywords hydrotherapy, blood pressure, and hypertension. Inclusion criteria are the range of publication years is in 2016-2020. While the exclusion criteria is when the independent variable used is a combination therapy. Based on a review of ten articles, hydrotherapy affects lowering blood pressure, therefore this therapy can be used as an adjunct therapy to lower blood pressure. This occurs because warm water dilates blood vessels, lowering blood pressure.